Classroom Management Skills of Physics Student Intern in SMK Negeri 5 Jember - Handayani, Rif’ati Dina (Proceeding of International Conference on Teacher Training and Education, 2016)
Classroom management is one of the tasks of teachers that are intended to create a conducive learning environment for students in the classroom. Classroom management skills have taken in this study is the skills related to the creation and maintenance of optimal learning conditions, and skills related to the development of learning conditions. To expand the ability of physics teacher candidate in classroom management, there was applied a lesson study. The subjects of this research are physics teacher candidates who are intern in SMKN 5 Jember. Data were taken by observation sheet, recording, and interviews. The assessment showed that the student intern has good score of 4.45 (scale 5.0).